INTEGRITATEA ÎN CONTEXTUL LIBERTĂȚII DE CONȘTIINȚĂ – NECESITATE ȘI/SAU IMPOSIBILITATE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Moral Uprightness in the Context of Freedom of Conscience - Prerequisite and/or UnattainabilityMoral uprightness is reffering to the whole ensemble of certainties, motivations and habits that have a firm ground in solid principles, norms and rules, historically and socialy determined, which are governing the way people are interacting and relate to each other, having as foundation one’s conscience and public opinion.In this article, following a short introduction, integrity is presented as a core moral value, seen from both an individual and public perspective, and also from that of the freedom of conscience. It also emphasizes some principles that should secure the moral uprightness in our post modern society.As far as the religious standpoint is concerned, the author stresses the fact the moral uprightness and freedom of conscience are both divine blessings, sacred gifts given for keeping in proper balance one’s self, necessary for having harmonious and fair associations with thouse that we live with andto grow lovesome liaisons with both other people and God.